Cancer Registration in the Middle East, North Africa, and Turkey: Scope and Challenges. (2021) - Abdul-Sater, Zahi; Shamseddine, Ali; Taher, Ali; Fouad, Fouad; Abu-Sitta, Ghassan; Fadhil, Ibtihal; Saab, Raya; Sullivan, Richard; Adib, Salim M.; Saleh, Shadi; Mukherji, Deborah
Abstract : PURPOSE: National cancer control strategies have been identified as essential tools for reducing and managing the growing burden of cancer in low- and middle-income countries. Cancer registration is an instrumental component of any cancer control strategy, providing the data to inform effective cancer policy. In the Middle East, North Africa, and Turkey (MENAT) region, cancer registration varies immensely and faces multifaceted challenges including protracted conflict. This study investigates and maps out the present capacities and outputs of cancer registration in the MENAT region and identifies thematic barriers facing implementation and utilization of cancer registry data. MATERIALS AND METHODS: We used a self-administered online survey with open and close-ended questions targeting national and institutional cancer registry managers in the MENAT countries. RESULTS: Registry managers from 19 MENAT countries reported the presence of 97 population-based, 48 hospital-based, and 24 pathology-based registries. Most population-based registries were well- or partially developed. Lack of accurate death records, complete medical records, and communication between stakeholders and deficiencies in trained personnel were critical challenges that were more severe in active conflict zones and neighboring conflict-affected regions. Cancer registration challenges included weak health infrastructure, absence of legislation mandating cancer registration, and disruption of cancer registration because of active conflict and loss of funding. Refugee host countries, such as Lebanon, Turkey, and Jordan, also reported conflict-related challenges including refugee mobility and lack of accurate data on forced migrants. CONCLUSION: This study provides a much-needed understanding of the current landscape and contextual challenges affecting cancer registration in the MENAT. These data are important for identifying areas on which to focus regional capacity-strengthening initiatives.